ATAOL BEHRAMOĞLU'NUN ŞİİRLERİNİN TEMATİK VE YAPI BAKIMINDAN İNCELENMESİ - NAMLI, TANER (Fırat Üniveristesi, 2004)
Ataol Behramoğlu, toplumcu şair ve yazarlarımızdandır. 1942 yılında Çatalca' da doğmuştur. Denemeci, tiyatro yazan, gazete yazan, araştırmacı ve şairdir. Fakat özellikle şiir alanındaki çalışmalarıyla tanınmıştır. Şiirinin özünü toplumcu gerçekçilik oluşturur. Bu nedenle şiirinde; toplumsal konular sıkça dile getirilir. Ataol Behramoğlu, 1960 toplumcu kuşağının önemli isimlerinden biridir. Çalışmamızın birinci bölümünde şairin hayatı ve edebi kişiliği hakkında bilgi verdik, ikinci bölümde şiirlerini tema ve yapı bakımından inceledik ve şiirlerinde öne çıkan temaları ve yapı unsurlarını ortaya koyduk. Üçüncü bölümde şiirlerini imaj bakımından inceledik. Bu çalışma sonucunda onun şiir dünyasını ortaya koymaya çalıştık. Anahtar kelimeler: Ataol Behramoğlu, edebi kişiliği, tema, yapı, imaj dünyası.

Ataol Behramoğlu, who was burn in 1942 in Çatalca, is one of the socialist poets and writers. He is a critic, a teatre writer, a jurnalist, a researcher and a poet. But he has especially known with his studies of sphere of poetry. His essence of poets constitute from socialist realizm. For this reason he often expressed social themes in his poems. Ataol Behramoğlu is one of the important persons of socialist poems generation of 1960's. In the first part of our work we gave some information about his life and literary personality. In the second part, we made a study concerning the themes, and structure of his poems and set aside his best themes. In the third part we researched his poems in respect of image. In consequense of this study try to set aside the world of his poems. The key words: Ataol Behramoğlu, literary personality, the theme, the structure, the world of image
A study on Ataol Behramoğlu's poetry from the point of view of themes and structure
Keywords: Türk Dili ve Edebiyatı; Turkish Language and Literature